Plasma interferon-γ concentration: a potential biomarker of disease activity of systemic chronic active Epstein-Barr virus infection - Uemura, Yu; Ohashi, Ayaka; Yoshimori, Mayumi; Nishio, Miwako; Hirakawa, Tsuneaki; Shimizu, Norio; Wada, Naomi; Imadome, Ken-Ichi; Arai, Ayako (Frontiers in Virology, 2022)
Systemic chronic active Epstein-Barr virus infection (sCAEBV) is an intractable disease that present activated EBV-infected T- or NK-cells and their clonal proliferation. When inflammatory symptoms persist and proceed, a lethal complication of hemophagocytic lymphohistiocytosis (HLH) develops, but its biomarker to represent the pathophysiology and an effective agent to cure have not been developed as of today. It is known that interferon-γ (IFN-γ) level in the peripheral blood increases in HLH correlatedly with the disease condition and that antagonistic anti-IFN-γ antibody is effective against HLH. We examined the plasma level of IFN-γ to investigate its role in the disease condition of sCAEBV. sCAEBV was diagnosed based on the criteria conforming to the definition of sCAEBV in the WHO classification issued in 2017. As it was previously reported, disease activity was defined as the condition positive for any one of the followings: fever, liver dysfunction, progressive skin lesions, vasculitis, and uveitis. Eighteen sCAEBV patients were examined. Their plasma IFN-γ levels were significantly higher than those of healthy donors. The levels in sCAEBV patients with disease activity were higher than those without disease activity. The mRNA expression of IFNG was detected in EBV-infected cells of all patients. We also detected a correlation between plasma IFN-γ levels and mRNA levels of EBV-infected cells in peripheral blood mononuclear cells. These results suggest that EBV-infected cells produce IFN-γ in sCAEBV. Although the difference was not significant, the patients whose plasma IFN-γ levels at diagnosis were higher than 40 pg/mL tended to result in poorer survival than those with lower levels. We concluded that plasma IFN-γ is a potential biomarker that indicates disease activity of sCAEBV. Further study shall confirm its significance.